SISTEM INFORMASI PENGELOLAAN SIMPAN PINJAM KOPERASI KARYAWAN BERBASIS WEB PADA PT. SINAR ABADI GAS - Muhammad Khaidir Fahram; Vina Vijaya Kusuma; Mulya Muthoyaroh (Journal of Innovation And Future Technology (IFTECH), 2024)
PT. Sinar Abadi Gas Cooperative is currently developing a web-based information system to expedite and facilitate savings and loan transactions. In this research, the team is using the research and development (R&D) method to develop a savings and loan application that will utilize PHP programming language and MySQL database. The team will create three types of users within this system, namely the admin, chairman, and members. They will have access to several prepared forms, including login forms for the admin, chairman, and members. Additionally, there will be customized main pages based on each user's role. The staff and member data forms will be used to manage cooperative member information. Furthermore, there will be a transaction form for savings and loans. These data will be used to generate member reports and loan reports. Cooperative members will also be able to apply for loans through the loan application form. After the application is submitted, the admin or chairman can utilize the confirmation form to follow up on the request. With this web-based cooperative data processing system, PT. Sinar Abadi Gas aims to enhance speed, accuracy, and precision in conducting savings and loan transactions.